2021
DOI: 10.1038/s41419-020-03338-4
|View full text |Cite
|
Sign up to set email alerts
|

eNOS-dependent S-nitrosylation of the NF-κB subunit p65 has neuroprotective effects

Abstract: Cell death by glutamate excitotoxicity, mediated by N-methyl-d-aspartate (NMDA) receptors, negatively impacts brain function, including but not limited to hippocampal neurons. The NF-κB transcription factor (composed mainly of p65/p50 subunits) contributes to neuronal death in excitotoxicity, while its inhibition should improve cell survival. Using the biotin switch method, subcellular fractionation, immunofluorescence, and luciferase reporter assays, we found that NMDA-stimulated NF-κB activity selectively in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…However, the S-nitrosylation of NMDA receptors resulted in decreased activity and inhibited downstream signaling pathways. 43 Following AS+TMP administration, we observed that SNO-NMDA receptors were increased, and the receptor activity might be inhibited to prevent calcium overload and thus protect neurons.…”
Section: ■ Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…However, the S-nitrosylation of NMDA receptors resulted in decreased activity and inhibited downstream signaling pathways. 43 Following AS+TMP administration, we observed that SNO-NMDA receptors were increased, and the receptor activity might be inhibited to prevent calcium overload and thus protect neurons.…”
Section: ■ Discussionmentioning
confidence: 87%
“…When ECM occurs, NMDA receptor activation increases glutamate metabolism and induces excitatory neurotoxicity, resulting in neuronal damage for the influx of large amounts of calcium ions. However, the S -nitrosylation of NMDA receptors resulted in decreased activity and inhibited downstream signaling pathways . Following AS+TMP administration, we observed that SNO-NMDA receptors were increased, and the receptor activity might be inhibited to prevent calcium overload and thus protect neurons.…”
Section: Discussionmentioning
confidence: 88%
“…As a result, the NF-κB-IκB complex remains inactive in the cytoplasm. Furthermore, p50 and p65 subunits of the NF-κB heterodimer are also inactivated via S-nitrosylation at Cys62 and Cys38, respectively ( Figure 3 A) [ 158 , 189 ]. Inactivation of these subunits inhibits their DNA binding for gene transcription.…”
Section: S-nitrosylation In the Tumor Micro-environmentmentioning
confidence: 99%
“…In particular, S-nitrosylation of caspase-1 inhibits the functions of NLR family pyrin domain containing 3 [NLRP3] inflammasome, which is an activation platform of caspase-1 [ 14 , 163 ]. It was shown that inhibiting NLRP3 inflammasome through caspase-1 S-nitrosylation was able to suppress angiogenesis, invasion and metastasis of melanoma and breast cancer cells [ 186 , 189 , 190 ].…”
Section: S-nitrosylation In the Tumor Micro-environmentmentioning
confidence: 99%
“…PTM of proteins based on redox reactions is a sophisticated and efficient mechanism conserved throughout evolution, which regulates intracellular signaling. Such modifications change the biological activity of downstream targets, modifying cellular processes such as autophagy [ 2 ], the immune and antioxidant response [ 3 , 4 ], energy metabolism [ 5 ], protein folding and degradation [ 6 ], proliferation and differentiation [ 7 , 8 ], and also affect the activity of transcription factors through direct and indirect mechanisms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%